Desenvolvimento e modelagem de um controlador fuzzy takagi-sugeno tolerante a faltas aplicado em veículos subaquáticos não tripulados - Carvalho, Eduardo Attuy (2018)
Despite the precautions taken during the design phase, the Autonomous Underwater Vehicles (AUV), object of study of this work, may suffer faults of its thrusters during the mission. This leads to losses, ranging from the excessive cost of maintenance to the loss of the vehicle. In order to deal with this type of problem, it is proposed the development of a Fault Tolerant Control (FTC) using Takagi-Sugeno fuzzy logic to compensate for the faults and failures of the thrusters in others that are healthy and in the same plane of action. Aiming to validate the developed control strategy, it has been applied in two AUV: Biointeractive-1(BA-1) and Nerov. Both vehicles have 6 thrusters, 4 horizontal and 2 vertical. Numerical simulations were carried out by using Matlab ® software into the Simulink ® package. For the vehicles traveled 20 meters on the x axis, taking into account the occurrence of fault and failure in the horizontal propeller 1 and fault in the propeller 4. The obtained results show that the compensation of the missing thrusters’ forces in the thrusters that are in the same plane of action guarantees the proper trajectory of the vehicles with accuracy and prevents abrupt oscillation of forces in the healthy thrusters.